TRI HITA KARANA IN THE PRINCIPLES OF GREEN ECONOMY TO ENHANCE THE COMPETITIVENESS OF MSMES - TM Kusuma; NW Deriani (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
Concept of the green economy as a strategy to enhance the competitiveness of MSMEs in Bali. Tri Hita Karana, which encompasses a harmonious relationship between humans and God, humans with fellow humans, and humans with the environment, serves as a foundation for creating sustainable business practices based on local values. The research method used is a qualitative approach with in-depth interviews of MSME actors, as well as observations of the application of these principles in business operations. Additionally, a quantitative approach is employed using multiple linear regression analysis. Data were collected through a survey of 100 MSME actors in Bali who have implemented the principles of Tri Hita Karana. The analysis results indicate that the application of Tri Hita Karana and the green economy model significantly positively affects the competitiveness of MSMEs. Specifically, these practices improve product differentiation, enhance customer trust, and support long-term business sustainability, thereby strengthening the market position of MSMEs in the face of regional and global competition.